2000
DOI: 10.1023/a:1006444105846
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Enterotoxigenic Escherichia coli (ETEC) produces a heat-stable enterotoxin (STa) that binds to and activates a putative intestinal receptor, guanylate cyclase, causing an increase in the intracellular levels of cyclic guanosine monophosphate (cGMP). Using flow cytometry and 125I-STa binding assays, we studied the distribution of STa-receptors on enterocytes isolated from different segments of the newborn calf's intestinal tract. We also investigated the effect of STa on the intracellular levels of cGMP and ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…We also showed that the lentil extract and yeast cell walls were able to sustain ETEC growth in M9 minimal medium, most likely due to the presence of non-fiber components, as E. coli strains are not able to degrade complex polysaccharides on their own [ 84 , 85 ]. We argue that this positive effect on pathogen growth may not be an issue in the context of the complex nutritional and microbial background of the distal small intestine, the main site of ETEC colonization [ 3 , 4 , 86 , 87 , 88 , 89 ]. In the human gut, fibers are degraded into smaller carbohydrates by the endogenous gut microbiota, providing substrates for pathogens, such as ETEC, which generally behave as secondary degraders [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that the lentil extract and yeast cell walls were able to sustain ETEC growth in M9 minimal medium, most likely due to the presence of non-fiber components, as E. coli strains are not able to degrade complex polysaccharides on their own [ 84 , 85 ]. We argue that this positive effect on pathogen growth may not be an issue in the context of the complex nutritional and microbial background of the distal small intestine, the main site of ETEC colonization [ 3 , 4 , 86 , 87 , 88 , 89 ]. In the human gut, fibers are degraded into smaller carbohydrates by the endogenous gut microbiota, providing substrates for pathogens, such as ETEC, which generally behave as secondary degraders [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diarrhea is a major problem in calves less than one month of age and is of tremendous economic importance. Diarrhea results in electrolyte imbalance, dehydration, and metabolic acidosis [16][17][18][19][20]; however, only a few studies available have focused on acid−base balance, serum chemistries, and blood gas parameters associated with diarrhea caused by infectious agents in neonatal calves [21,22]. Unfortunately, because the information currently available for healthy young Korean native calves is not well documented, reference values for adult cattle have commonly been used to direct therapy.…”
Section: Discussionmentioning
confidence: 99%
“…NAG/O1-ST binds to guanylyl cyclase C (GC-C) on the apical surface of enterocytes, signals intracellular cGMP, and a cGMP-dependent kinase (PGKII) to phosphorylate CFTR on the apical membrane. The activation of cGMP and CFTR signaling stimulates chloride and fluid secretion (Al-Majali et al, 2000 ). PGKII plays an important role in regulating cGMP-dependent translocation of CFTR and ST-dependent anion secretion, which is independent of CT regulation (Golin-Bisello et al, 2005 ).…”
Section: Major Toxins Produced By V Cholerae and mentioning
confidence: 99%